Watershed restoration as a tool for improving coral reef resilience against climate change and other human impacts. (20th December 2016) - Shelton, Austin J.; Richmond, Robert H.
Abstract: Environmental stressors in coastal areas threaten the sustainability of marine resources and reduce their resilience to climate change impacts. Accelerated land erosion is a major stressor that leads to increased turbidity and sedimentation on downstream coral reefs and the degradation of ecosystem functions. Volunteers from a community-based initiative in Guam installed 130 tree seedlings and 54 m of sediment filter socks in eroding hillsides above Fouha Bay, to reduce erosion. A soil probing method for measuring soil depth was developed and used to evaluate the effectiveness of the watershed restoration tools. The trees and socks trapped 111.8 tons of sediment on land after 21 months. In heavily eroding portions of the restoration plot, where socks and trees were used in combination, the mean sediment trapping efficiency was 44 kg m −2  yr −1 . Previous studies indicate a 75% reduction in sedimentation rate is required to bring Fouha Bay below severe-catastrophic sedimentation stress (>50 mg cm −2  day −1 ). Based on the observed sediment trapping efficiency of restoration tools in this study, an estimated 0.05 km 2 of severely eroding hillsides must be treated with 19 km of socks and 11, 000 trees to trap 2121 tons of sediment and achieve the necessary reduction. If sediment input into the bay is controlled, existing sediment will clear out with storm-driven swells. As shown in other high islands, coral reefs are resilient and can recover after sedimentation stress is reduced. Data generated on the efficiency of watershed restoration tools in this study can be used in watershed management plans to promote the sustainability and resilience of coastal areas in other tropical islands. Graphical abstract: Highlights: Erosion control techniques were tested as watershed restoration strategies. A soil probing method for measuring soil depth was developed. The total sediment trapped on land through erosion control was determined. We suggest how to use the tools to reduce sedimentation impacts on Fouha Bay coral reefs and elsewhere.